PELAKSANAAN MODEL MAKE A MATCH DALAM MENINGKATKAN HASIL BELAJAR - Marpaung, Tiodor (JURNAL PENA EDUKASI, 2018)
Abstract: The background of this research is still the lack of understanding of teachers about techniques and ways to integrate national character development in teaching and learning activities, especially at SD Negeri 014682 Perhutaan Silau. The objectives of the School Action Research are: (1) Review of the Principal Supervision of the Implementation of the Make A Match Method by PKn Teachers in Improving the Learning Achievement of Grade V Students of SD Negeri 014682 Perhutaan Silau district Pulo Bandring academic year 2017/2018; (2) Carry out an analysis of PKn Teachers in teaching and learning activities which have implications for increasing student participation or activity towards the implementation of national character building values, such as the value of hard work, cooperation, mutual respect and so on. Data was collected through observation, interviews, tests, and documentation studies. The school action research was carried out in 2 cycles, consisting of planning, implementing actions, observing and reflecting. Keywords: Make A Match, Learning Achievement Abstrak: Penelitian ini dilatar belakangi masih kurangnya pemahaman guru tentang teknik dan cara mengintegrasikan pembangunan karakter bangsa dalam kegiatan belajar mengajar, khususnya di SDN 014682 Perhutaan Silau. Adapun tujuan dari Penelitian Tindakan Sekolah ini adalah: (1) Peninjauan Supervisi Kepala Sekolah Terhadap Pelaksanaan Metode Make A Match Oleh Guru PKN Dalam Meningkatkan Prestasi Belajar Siswa Kelas V SDN 014682 Perhutaan Silau kec. Pulo Bandring TP. 2017/2018; (2) Melaksanakan analisis terhadap Guru PKN dalam kegiatan belajar mengajar yang berimplikasi pada peningkatan partisipasi atau keaktifan siswa terhadap keterlaksanaan nilai-nilai pembangunan karakter bangsa, seperti nilai kerja keras, kerjasama, saling menghargai dan sebagainya. Data dikumpulkan melalui observasi, wawancara, test, dan study dokumentasi. Penelitian tindakan sekolah ini dilaksanakan dalam 2 siklus, terdiri dari perencanaan, pelaksanaan tindakan, pengamatan dan refleksi. Kata kunci: Make A Match, hasil belajar